Efficiency Of Zakat Institutions In Indonesia During 2017-2021: An Application Of Data Envelopment Analysis - Fakhri, Muhammad Yusuf; Bahri, Efri Syamsul; Wulan, Mulyaning (Jurnal Akuntansi dan Keuangan Islam, 2023)
The purpose of this study is to measure the financial performance of the National Amil Zakat Institution (LAZNAS) in the effectiveness of distribution and the efficiency of fund management. This research method uses quantitative with a descriptive approach. This study uses secondary data derived from LAZNAS website sources. The technique of collecting data by purposive sampling, namely; LAZNAS, which can publish financial statement data on the website from 2017-2021. Analysis technique or financial performance on effectiveness using the Allocation to Collection Ratio (ACR) approach. Then, the efficiency aspect uses the Data Envelopment Analysis (DEA) approach. The results of measuring financial performance in the part of effectiveness show that 6 LAZNAS in the Highly Effective category are; Dompet Dhuafa, Griya Yatim Dhuafa, LAZISNU, Panti Yatim Indonesia, Rumah Yatim, and Rumah Zakat. Then, Al Azhar and LAZISMU showed the Effective category in the 2017-2021 period. On efficiency measurements, LAZISNU already offers efficiency. Other LAZNAS are still experiencing inefficiencies in the 2017-2021 period.